The Challenges and Opportunities of Integrating Islamic Values into Business Education: A Systematic Literature Review - Juliansyah Juliansyah (Penelitian dan Pengembangan Ilmu, 2024)
This research examines the impact of integrating Islamic values in business education on business performance and company competitiveness through a systematic literature review. The article selection process uses the PRISMA method and certain inclusion criteria. The results show that the integration of Islamic values improves business performance and corporate competitiveness through the promotion of a moral environment and economic justice. The implication of this research is the need to emphasize the application of Islamic values in business practices and business education. The challenges and limitations of this study highlight the need for further research. Future research is expected to provide deeper insight into the role of Islamic values in inclusive global business.